Antibacterial Activity of Coffee Arabica (Coffea arabica L.) Fruit Skin Methanol Extract On Bacteri Eschericia coli and Staphylococcus aureus - Rita Maliza; Jannati Aulah; Oktira Roka Aji (Bioscience, 2020)
Coffee fruit skin is a waste from coffee bean processing. Arabica coffee bean extract (Coffea arabica L.) is known to contain anthocyanin compounds, polyphenols, beta-carotene, and vitamin C which have the potential as antimicrobial agents. The purpose of this study is identification and anaysis the optimal concentration of Arabica coffee peel extract which inhibits the bacteria Escherichia coli and Staphylococcus aureus. This study used an experimental method consisting of 3 extract concentration treatments, positive control, and negative control with 3 repetitions. The treatments tested were 25%, 50%, 75% coffee fruit peel, negative control (sterile distilled water) and positive control (Ampicillin 2 µg / ml). The bacterial test was carried out using the in vitro method. The parameters measured were the amount of inhibition zone (mm) formed on the Mannitol Salt Agar (MSA) and Mac Conkey media. Analysis of research data using the One-way ANOVA test and Duncan test at α = 0.05. The results showed that the optimum concentration of the extract against Staphylococcus aureus was 50%, while the optimum concentration of Escherichia coli was 25%. The results of this study indicate that the extract can be an antibacterial that can inhibit the growth of Escherichia coli and Staphylococcus aureus bacteria optimally.